Strategies for Implementing Integrated Management System in the Malaysian Manufacturing Companies - Mohammad, Musli (2006)
Integrated Management System (IMS) is one of the approaches to gain competitiveness and enter the free trade markets. By implementing IMS, several business related management systems such as Quality Management System (QMS), Environmental Management System (EMS) and Occupational Health and Safety Management System (OHSMS) could be integrated in order to satisfy a variety of stakeholders. The main purposes of this study were to assess the status of IMS implementation, investigate the implementation of IMS and propose the strategies for implementing IMS in the Malaysian manufacturing companies. Survey was employed to collect data on the status of IMS implementation, the IMS strategies that have been used and the strategies that should be used by the companies. Questionnaires were distributed to 87 companies that are certified with both IS09000 and IS014000, which resulted in a response rate of 36.8%. Three case studies were conducted at the manufacturing companies that have implemented IMS, in order to know how the IMS strategies have been implemented by them. For the status of IMS implementation, the results from the survey indicate that only 46.9% of the manufacturing companies that are certified with IS09000 and IS014000 have implemented IMS and the level of practice is moderate. Most of these companies (92.3%) have implemented IMS for a period of not more than three years, which could be considered as new. This study has also revealed the strategies for implementing IMS in the Malaysian manufacturing companies. Based on the survey results, it was found that the companies should start with implementing the management systems individually and then followed by integration. The sequence of integration should starts with establishing the QMS first. It is followed by integrating the EMS with the existing QMS (EMS + QMS = QEMS), and finally integrating the OHSMS with the existing QEMS (Quality and Environmental Management System). In terms of the types of integration, the companies should utilise 111 integration. The companies should also use the management system standard approach (IS09000, IS014000 andlor OHSAS18000) as a basis for integrating the management systems. Five most Critical Success Factors (CSFs) for IMS implementation are: management commitment and leadership, education and training, continual improvement, performance measurement, and systems and processes. The main barriers for implementing IMS are: lack of trained and experience staff to implement MS, lack of time to devote to IMS initiatives, and lack of employees' awareness and understanding on IMS implementation. Most of the results obtained from the survey are consistent with the results from the case study, except for the types of integration. Even though the results from the survey indicate that the companies should use full integration, it was found that all the case companies have been using partial integration. This project culminates with conclusions, suggestion of steps for implementing IMS in the manufacturing companies and future research recommendations.